2014
DOI: 10.1097/fpc.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

The effects of CES1A2 A(−816)C and CYP2C19 loss-of-function polymorphisms on clopidogrel response variability among Chinese patients with coronary heart disease

Abstract: The CES1A2 -816C and the CYP2C19 LOF alleles were associated with attenuated platelet reactivity to clopidogrel. CYP2C19 LOF was also predictive of ST; however, the association between the CES1A2 -816C allele and development of ST requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 28 publications
0
28
1
Order By: Relevance
“…Several recent studies report an impact of CES1 polymorphisms on clopidogrel response in patients (Lewis et al, 2013b; Tarkiainen et al, 2015; Xie et al, 2014; Zou et al, 2014). This is consistent with findings of the PAPI study, which show that clop-AM plasma concentrations are significantly higher in CES1 G143E-allele carriers vs. wild-type subjects (30.3 ± 6.1 vs. 19.0 ± 0.4 ng/ml, P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies report an impact of CES1 polymorphisms on clopidogrel response in patients (Lewis et al, 2013b; Tarkiainen et al, 2015; Xie et al, 2014; Zou et al, 2014). This is consistent with findings of the PAPI study, which show that clop-AM plasma concentrations are significantly higher in CES1 G143E-allele carriers vs. wild-type subjects (30.3 ± 6.1 vs. 19.0 ± 0.4 ng/ml, P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Despite control for various polymorphisms besides those in ABCB1, and for lifestyle factors and co-medications, the variability has remained largely unexplained. With regard to outcome, several clopidogrel trials have been published, but the results were inconsistent and mostly not significant [164][165][166]. Nonetheless, Simon et al [157] reported an association between the 3435TT genotype and an increased risk of cardiovascular events.…”
Section: Clopidogrelmentioning
confidence: 97%
“…In patients with acute coronary disease under clopidogrel treatment, the on-treatment platelet reactivity in the individuals carrying the CES1 143E-allele was also significantly lower than that in 143G-homozygotes [68]. On the other hand, the CES1A -816A/C allele, which has been reported to cause significantly enhanced transcriptional activity of CES gene [69], has been found to be associated with either significantly increased or reduced on treatment platelet reactivity in patients with coronary heart disease [70, 71]. These findings suggests that more research needs to be done to conclusively characterize the impact of genetic polymorphism in CES1 on clopidogrel response.…”
Section: Covariates That Affect Clopidogrel Dose/pk/pdmentioning
confidence: 99%